2024 dawns in the midst of myths, massacre, and melancholia - Muhsin, Sayyed Mohamed (Mission Soft Foundation, 2024)
Hope remains the fuel for our voyage to the future. As we embark on the journey of the new year, let's aspire to make it one of enrichment, productivity, and greatness. It's opportune to pause and scrutinize the reality that envelops us. This reflection serves as a guide to liberate ourselves from any misconceptions that may have entangled our lives. Placing hope in myths and misconceptions can worsen our suffering. Let’s approach future challenges thoughtfully.